A De Novo MITF Deletion Explains a Novel Splashed White Phenotype in an American Paint Horse. (2nd April 2020) - Magdesian, K Gary; Tanaka, Jocelyn; Bellone, Rebecca R
Abstract: Splashed white is a coat color pattern in horses characterized by extensive white patterning on the legs, belly, and face often accompanied by blue eyes and deafness. Three mutations in microphthalmia-associated transcription factor (MITF ) and two mutations in Paired Box 3 (PAX3 ) have been identified that explain splashed white patterns (SW1–SW5). An American Paint Horse stallion with a splashed white phenotype and blue eyes, whose parents were not white patterned, was negative for the 5 known splashed white variants and other known white spotting alleles. This novel splashed white phenotype (SW6) was hypothesized to be caused by a de novo mutation in MITF or PAX3 . Analysis of whole-genome sequencing using the EquCab3.0 reference genome for comparison identified an 8.7 kb deletion in MITF on ECA16 (NC_009159.3:g.21551060-21559770del). The deletion encompassed part of intron 7 through the 3′ UTR of exon 9 of MITF, including the helix-loop-helix DNA-binding domain (ENSECAT00000006375.3). This variant is predicted to truncate protein and impair binding to DNA. Sanger sequencing confirmed the stallion was heterozygous for the MITF deletion. No single nucleotide polymorphisms (SNPs) or structural variants were identified in PAX3 or any of the other candidate genes that were unique to the stallion or predicted to affect protein function. Genotyping five of the stallion's splashed white offspring, including one all white foal, found that they were also heterozygous for the deletion. Given the role of MITF in producing white pattern phenotypes, and the predicted deleterious effect of this mutation, this 8.7 kb deletion is the likely causal variant for SW6.